O tom de divulgação narrativa sob a ótica da teoria do alto escalão: evidências no Brasil - Lopes, Alex Ferreira (2022)
The objective of this study was to evaluate the key factors of the narrative disclosure tone contained in the press releases of publicly traded companies in Brazil from the perspective of the characteristics of their respective CEOs, based on the Upper Echelons Theory. To this end, computerized textual analysis was used, using the bag-of-words methodology, to measure the frequency of words with a positive and negative tone in the analyzed reports to form the dependent variables of the research. The characteristics of CEOs and other non-financial research variables were collected through documents delivered to the Securities and Exchange Commission (CVM), more specifically in the Reference Forms. Financial information was collected through the Thomson Reuters and Economatica databases. The final sample had 1303 observations-year during the period 2011 - 2020 and the final analysis of the variables was performed using ordinary least squares (OLS) regressions. The results showed a significant association between the variables of interest and explanatory variables, but with an inverted sign. Contrary to what the literature preaches, the variables of characteristics of CEOs such as age, financial expertise and female executive did not show an inverse association with the tone of narrative disclosure of the companies' earnings reports. However, Corporate Governance mechanisms, such as the audit committee and board independence, proved to be important factors in determining the positive tone of the companies’ press releases in the sample. In addition, it has also been shown that CEOs with narcissistic traits are more likely to evince a more optimistic tone towards those who do not have these traits.